Problems and Coping Mechanism among Students and Teaching Personnel in Trece Martires City College - Romen, Virginia C. (Journal of Research and Investigation in Education, 2025)
Coping in the midst of pandemic may be a new phenomenon especially in the case of teachers and students in the tertiary education. There is a need to understand this phenomenon to better improve ways by which people in the academe could overcome the challenges brought about by the global crisis. This study aimed to identify problems experienced by students and teaching personnel of Trece Martires City College most especially at this time of pandemic. Thus, this study was conducted to investigate the problems and, likewise, the coping mechanism employed by the respondents. Using the survey-questionnaire based from Madhuleena Roy Chowdhury’s study (2019), 298 students and 36 teaching personnel of TMCC were surveyed. Data gathered were analyzed using frequency counts, percentages, weighted means, and ranking. Results show that most of the student-respondents were female, were in the appropriate age to attend college, and belong to a family whose income is P10,000 and below. Meanwhile, most of the faculty-respondents were female, belong to a diverse age range, belong to a family whose income is P12,000.00 to P49,999.00, and were Bachelor’s Degree holders. Results also revealed that health and safety problems were perceived to be the most challenging problem among both the student-respondents and teacher-respondents. In terms of coping mechanism in a pandemic situation, both groups of respondents reported that they mostly employ the coping mechanism of thinking and acting positively, followed by being more religious for the students; and for teaching personnel, soliciting advice from family and friends.